Arab Spring: Islam dalam gerakan sosial dan demokrasi Timur Tengah - Shafira Elnanda Yasmine (Faculty of Social and Political Science, Universitas Airlangga, 2015)
Social movement during Arab Spring has lead to political uprising in Middle East. Started from Tunisia, the revolt spread to neighboring states such as Egypt, Libya, also Syiria. Influenced by religion and strong Islamic tradition, protestors demand the presence of democracy within political system which had held autocracy as ruling system for decades. It is commonly assumed that democracy and Islam were mostly incompatible, moreover in a state whose Islamic values has deeply rooted in the daily life of its people. This article focuses in the usage of Islamic values within global civil society movement in Arab Spring. Theory of Islam and Ideology were applied to analyze the phenomena. Having view the revolution generally, this research found that Arab Spring is required as a phase which led Islam into particular flexibility level towards democracy and brought democratization into the Arab world. This article resulted in the conclusion that trigger a revolution not because of religious affairs, the demonstrators were joined not one hundred percent Muslim, and the issues that required not related to the religious life of the community, but Islam is either the value or the practice of worship, can not be separated in the organization of the masses during the revolution.